Optimization of salt washing protocols for surimi production from invasive blackchin tilapia (Sarotherodon melanotheron): Molecular and functional properties - Senphan, Theeraphol; Mungmueang, Natthapong; Hoque, Md Sazedul; Sriket, Chodsana; Benjakul, Soottawat; Buamard, Natchaphol; Leelapongwattana, Kittima; Nalinanon, Sitthipong (My University, 2025)
This study presents the first systematic molecular characterization and protein chemistry optimization for surimi processing from invasive blackchin tilapia (Sarotherodon melanotheron), introducing novel salt washing protocols. Ten treatments were evaluated including conventional washing, single/multiple salt washing (0.3–0.9 % NaCl), and pH-shifting methods. Molecular analyses (SDS-PAGE, ATR-FTIR and SEM) revealed myofibrillar protein preservation and distinct structural modifications. The optimized 0.6 % NaCl protocol achieved selective heme protein removal while preserving myofibrillar integrity, yielding superior gel chemistry (whiteness: 76.47 vs. 71.04) and highest sensory acceptance (7.33 vs. 6.40). pH-shifting enhanced protein recovery (68.59 %) but caused molecular aggregation and network disruption, reducing gel strength by 82 %. Molecular analysis demonstrated that salt washing selectively removes chromoproteins while preserving essential gel-forming proteins, whereas pH-shifting caused protein aggregation. SEM confirmed dense protein matrices in salt-washed samples versus fragmented networks in pH-treated surimi. This chemistry-guided approach transforms invasive species into functional protein ingredients.
Keywords: Blackchin tilapia; Gel properties; Invasive species; pH-shifting; Salt washing; Surimi; Value-added products